2013
DOI: 10.1080/09669760.2013.867170
|View full text |Cite
|
Sign up to set email alerts
|

Engaging children's participation in and around a new music technology through playful framing

Abstract: This article concerns children's engagement and participation in a musical dialogue, with the adult taking the role of the more-experienced participant and frames the activity as a musical play activity (in both senses of the word 'play'). It presents an analysis of empirical data from a session with two six-year-old children interacting with and around a new music technology in a Swedish preschool setting and explores what participating in these practices implies for the children's learning. The results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The teachers' role for children's learning in music from this perspective is to provide opportunities for musical experiences. This can be done by the teachers communicatively framing activities in a playful manner so that children are engaged, and then introduce them to mediating tools as a way of discerning musical aspects (Lagerlöf, Wallerstedt, & Pramling, 2013). Such musical aspects are, for example, dynamics, tempo and timbre.…”
Section: Introductionmentioning
confidence: 99%
“…The teachers' role for children's learning in music from this perspective is to provide opportunities for musical experiences. This can be done by the teachers communicatively framing activities in a playful manner so that children are engaged, and then introduce them to mediating tools as a way of discerning musical aspects (Lagerlöf, Wallerstedt, & Pramling, 2013). Such musical aspects are, for example, dynamics, tempo and timbre.…”
Section: Introductionmentioning
confidence: 99%
“…Also in the musical domain, "the playful experience of working with music technology, together with the rewarding sounds that can be produced by it, provide strong motivators for young children to experiment and develop their musical ideas" (Rowe et al, 2017;reported in Liu-Rosenbaum and Creech, 2021, p. 436). Notably, studies exploring the potential of the MIROR-Impro system (a program that enables interactive improvised musical dialogs with a computer) suggest that experiences with music technology are particularly rewarding for children when they are shared with their peers or teachers (Wallerstedt and Lagerlöf, 2011;Lagerlöf et al, 2013). Also, research focusing on adult engagement with music suggests that, rather than skill acquisition, this group especially values a strong focus on social interaction and musical enjoyment (Roulston et al, 2015;Zhukov, 2021).…”
Section: Practice At Home Playfulness and Social Interactionmentioning
confidence: 99%
“…Music is considered as amongst the greatest source of education (Elizabeth, 2016) as it creates a positive environment that supports self-control and self-efficacy. Music, art and creativity should not be separated from young children's life and learning as these activities provide them with a fun yet meaningful experience (Lagerlöf et al, 2013).…”
Section: Research Backgroundmentioning
confidence: 99%